POST-QUANTUM THREATS TO INFORMATION SECURITY: CHALLENGES AT THE GLOBAL AND NATIONAL LEVELS - Prokopovych-Tkachenko, D. I.; Khrushkov, B. S.; Derkach, Y. O. (Systems and Technologies, 2025)
The article examines the key aspects of the impact of quantum computing on modern information security, as well as the potential consequences of its implementation in various spheres of public life. In particular, it analyzes the risks arising from the possibility of breaking traditional cryptographic algorithms, such as RSA, DSA, ECC, and others, using quantum computers capable of performing computations at unprecedented speeds. This poses a threat to the confidentiality, integrity, and availability of information in financial, governmental, military, and other critically important systems. The study proposes solutions to address issues related to the implementation of quantum-resistant cryptography. It out-lines the prospects of using algorithms based on lattices, error-correcting codes, multivariate equations, isogenies of elliptic curves, and other approaches capable of ensuring long-term data security. International initiatives for the standardization of post-quantum cryptographic technologies are considered, with particular emphasis on the NIST program for the development of new cryptographic standards.Special attention is paid to the challenges faced by countries at the national level. These include the need to modernize existing information systems, develop new cybersecurity standards, train specialists in quantum technologies, and address significant financial and organizational costs. Risks are highlighted for financial, energy, transportation, and governmental infrastructures that are critically dependent on reliable cryptographic protection methods. The article emphasizes the importance of international cooperation in addressing global post-quantum threats. Mechanisms for international exchange of experience, joint research, and the formation of alliances to accelerate the implementation of quantum-resistant technologies are proposed. The necessity of developing new cybersecurity strategies that account for future challenges and ensure the stability of modern information systems in the post-quantum era is explored.